Age and growth of the bigeye thresher shark, Alopias superciliosus, from the pelagic longline fisheries in the tropical northeastern Atlantic Ocean, determined by vertebral band counts - Fernandez-Carvalho, Joana (2016)
The bigeye thresher, Alopias supercilious, is commonly caught as bycatch in pelagic longline fisheries targeting swordfish. Little information is yet available on the biology of this species, however. As part of an ongoing study, observers sent aboard fishing vessels have been collecting set of information that includes samples of vertebrae, with the aim of investigating age and growth of A. supercilious. A total of 117 specimens were sampled between September 2008 and October 2009 in the tropical northeastern Atlantic, with specimens ranging from 101 to 242 cm fork length (FL) (176 to 407 cm total length). The A. supercilious vertebrae were generally difficult to read, mainly because they were poorly calcified, which is typical of Lamniformes sharks. Preliminary trials were carried out to determine the most efficient band enhancement technique for this species, in which crystal violet section staining was found to be the best methodology. Estimated ages in this sample ranged from 2 to 22 years for females and 1 to 17 years for males. A version of the von Bertalanffy growth model (VBGF) re-parameterised to estimate L(0), and a modified VBGF using a fixed L(0) were fitted to the data. The Akaike information criterion (AIC) was used to compare these models. The VBGF produced the best results, with the following parameters: L(inf) = 293 cm FL, k = 0.06 y(-1) and L(0) = 111 cm FL for females; L(inf) = 206 cm FL, k = 0.18 y(-1) and L(0) = 93 cm FL for males. The estimated growth coefficients confirm that A. supercilious is a slow-growing species, highlighting its vulnerability to fishing pressure. It is therefore urgent to carry out more biological research to inform fishery managers more adequately and address conservation issues.